1994
DOI: 10.1128/iai.62.10.4690-4694.1994
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma arginini TUH-14 membrane lipoproteins induce production of interleukin-1, interleukin-6, and tumor necrosis factor alpha by human monocytes

Abstract: Mycoplasma arinini TUH-14 partially purified membrane lipoproteins (TUH-14-pp) directly induce secretion of the cytokines involved in the inflammatory response, namely, interleukin 1 (IL-1), tumor necrosis factor alpha, and IL-6, by human monocytes cultured in the absence of serum. The biological activity of each cytokine correlates with its immunoreactivity. Upon stimulation with either TUH-14-pp or lipopolysaccharide, most tumor necrosis factor alpha and IL-6 is secreted in the extracellular compartment, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…Also, infections with cell wall-free mycoplasmas may be associated with strong inflammatory reactions. Recently, some reports demonstrated the macrophage-stimulatory activity of mycoplasmas or mycoplasmaderived lipoprotein fractions in vitro (9,16,26), suggesting that mycoplasma lipoproteins may be directly responsible for the induction of cytokines and chemokines. In this study, we used MALP-2, a chemically well defined prototype of a mycoplasma-derived lipopeptide, and investigated in detail the spectrum of inflammatory mediators that were released in response to this compound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, infections with cell wall-free mycoplasmas may be associated with strong inflammatory reactions. Recently, some reports demonstrated the macrophage-stimulatory activity of mycoplasmas or mycoplasmaderived lipoprotein fractions in vitro (9,16,26), suggesting that mycoplasma lipoproteins may be directly responsible for the induction of cytokines and chemokines. In this study, we used MALP-2, a chemically well defined prototype of a mycoplasma-derived lipopeptide, and investigated in detail the spectrum of inflammatory mediators that were released in response to this compound.…”
Section: Discussionmentioning
confidence: 99%
“…However, also preparations from mycoplasmas can powerfully stimulate macrophages/monocytes (2,6,15,33,34), although these microorganisms lack a cell wall. Recently, several reports demonstrated that crude fractions of lipoproteins derived from different mycoplasma strains showed macrophage-stimulatory activities by inducing the production of proinflammatory cytokines (9,16,26). In a more detailed analysis, the lipopeptide MALP-2 (macrophage-activating lipopeptide 2), recently isolated from a clone of Mycoplasma fermentans, has been shown to induce proinflammatory cytokines as well as nitric oxide release from mouse peritoneal macrophages (23).…”
mentioning
confidence: 99%
“…In many aspects, this material resembled the mycoplasma-derived highmolecular-weight material (MDHM) which was isolated from M. fermentans by virtue of its macrophage-stimulatory activity (25) and which turned out to be a mixture of lipopeptides (26). It has been previously observed that mycoplasmas, like other microorganisms, produce components which activate macrophages (10,18,20,38) and that they induce inflammation under various natural or experimental conditions (13,16,19,42). In continuation of previous work on MDHM, a welldefined lipopeptide, named 2-kDa macrophage-activating lipopeptide (MALP-2), was isolated from M. fermentans and purified.…”
mentioning
confidence: 91%
“…OMPs of Shigella £exneri induced murine macrophages to release TNF-K and IL-6 [29]. Shiga like toxin [30], cell wall glycoproteins [31] and lipoproteins from a number of bacteria [32,33] released several cytokines from human monocytes, murine macrophages and mouse macrophage cell line. Apart from proteins, there have been reports that bacterial PS induced IL-1 release from murine macrophages [34,35] or other cytokines from human PBMC [28].…”
Section: Discussionmentioning
confidence: 99%